Participatory Digital Gameplay Narrative Design for Public Space Sustainability Management: Empirical Research with Primary School Children - Tragazikis, Panagiotis; Gouscos, Dimitris (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
This paper reports results of completed research with primary school children which took place in Athens, Greece. Children engaged in designing the play experience of digital mini-games corresponding to episodes/missions of an entire plot. The games were coded by the school teacher on low-end mobile phones using AppInventor and were then played by children designers and testers. The game plot concerned restoring management rules for a public space (an urban park), along sustainability principles. The results focused on the participation processes of children in critical game narrative design, and decision-making about public space management alternatives to embed in game narrative design.